Effects of CEO Turnover in Banks: Evidence Using Exogenous Turnovers in Indian Banks. (5th November 2018) - Sarkar, Arkodipta; Subramanian, Krishnamurthy; Tantri, Prasanna
Abstract : We examine the effects of chief executive officer (CEO) turnover in banks. Incoming bank CEOs face problems of information asymmetry because banks' operations are opaque and bank risk can change dramatically in a short time. These CEOs may therefore change bank policies to manage their personal risks. Since CEO turnover is usually endogenous, we utilize a setting in which CEO turnover is based solely on retirement age and is thus exogenous to bank performance. Consistent with our thesis, incoming CEOs increase provisioning for future delinquencies and shrink lending. Bank stock prices decline following these changes. Politically motivated lending or ever-greening cannot explain our results.